Degenerative Spondylolisthesis in the Fifth Lumbar Vertebra and Radiographic Parameters: A Correlation Analysis. Issue 9 (November 2017) - Chen, Qian; Cao, Lu; Bian, Chong; Wang, Hui-Ren; Lin, Hong; Li, Xi-Lei; Jiang, Yun-Qi; Dong, Jian
Abstract : Study Design: A retrospective study. Objective: This study aimed to analyze the relationships between degenerative spondylolisthesis in the fifth lumbar vertebra (L5-DS) and radiographic parameters and to further determine the radiographic predictors of the development of L5-DS. Summary of Background Data: Degenerative lumbar spondylolisthesis (DLS) is a common degenerative disease of the spine; however, the correlations between L5-DS and radiographic parameters remain controversial. Patients and Methods: This retrospective case-control study was conducted in our hospital. Between 2011 and 2014, a total of 84 subjects with L5-DS were enrolled in the DLS group, and 56 healthy volunteers were recruited to the control group. A series of radiographic parameters, including the bone mineral density, disk degenerative index, disk height, L5 vertebral size (L5-VS), lumbar lordosis angle (LL), sacral slope angle (SS), pelvic incidence (PI), facet joint angulations (FJA) of the cephalad and caudad portions, and asymmetry of the FJA, were measured in both groups by 3 examiners. Results: The bone mineral density, disk degenerative index, disk height, L5-VS, LL, SS, PI, and FJA exhibited significant differences ( P =0.014–0.045) between the DLS and control groups. Significant changes in the FJA of the cephalad and caudad portions in the L4–L5 and L5–S1 segments were observed between the 2 groups ( P =0.00, 0.00), whereas no significant differences in the asymmetries of FJA were observed in the L4–L5 or L5–S1 segments ( P =0.605–0.972). Among all of the parameters, the L5-VS ( P =0.025), SS ( P =0.020), LL ( P =0.031), PI ( P =0.014), and FJA ( P =0.022) were identified as being associated with the DLS group by multiple logistic regression analysis. Conclusions: In this study, SS, LL, PI, and a more sagittal FJA were proven to be risk factors for L5-DS, whereas L5-VS was found to be a likely protective factor against L5-DS. These parameters should be considered predictors of L5-DS.